ANALISIS HUBUNGAN INDIKATOR FUNDAMENTAL MAKRO EKONOMI AMERIKA SERIKAT TERHADAP NERACA PERDAGANGAN INDONESIA - Devi Novita Sari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aimed to see the causality between macro economy fundamental indicators of United States towards trade balance of Indonesia. This study is using Vector Error Correction Model (VECM) model with yearly data from 1983 to 2015. The result of this study, there is causality between macro economy indicators such as inflation, foreign direct investment, gross domestic product and global inflation growth towards trade balance of Indonesia in long term. By the variance decomposition, inflation gives the biggest impact towards trade balance than the other variables.Key words: Inflation, GDP, FDI, trade balance, VECM, Vector Error Correction Model